Two new species of Afrodacarellus (Acari: Mesostigmata: Rhodacaridae) from Brazil and a key to the world species of the genus - Santos, Marcia D. Dos; Castilho, Raphael C.; de Moraes, Gilberto J.; Silva, Edmilson S. (Zootaxa, 2017)
Within a project to determine the edaphic predatory mites from the Brazilian Alagoas state, two new species of Afrodacarellus Hurlbutt (Rhodacaridae) were found, namely Afrodacarellus alagoensis Santos & Castilho n. sp. and Afrodacarellus xucurukariri Santos & Castilho n. sp.. These are here described based on the morphology of adult females. A key for the separation of females of the 31 recognisable world species of Afrodacarellus is provided, including the newly described species.